2015
DOI: 10.3390/environments2040449
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Willingness to Pay for Cabbage with Minimized Pesticide Residues in Southern Benin

Abstract: Cabbage (Brassicaceae) is one of the most frequently consumed exotic vegetables in Benin and also the most affected by insects. To meet growing food demand, farmers rely heavily on synthetic pesticides that are harmful for themselves, consumers and the environment. Integrated pest management has been proposed as the means to improve vegetable productivity and quality in many developing countries. One approach is to substitute pesticides with physical barriers to insects, like nets. Here, we assess consumers' O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 80 publications
2
14
0
1
Order By: Relevance
“…Similar profits to those obtained in the open field were only simulated by increasing the selling price by 50%. This confirmed a previous cost-benefit analysis conducted in Benin showing that the profitability of low tunnels for cabbage cultivation relies on the capacity to value the quality of products on the market (Vidogbéna et al, 2015a;Vidogbéna et al, 2015b). The higher profitability of the use of low tunnels reported in that study was also explained by higher insecticide costs, US $0.31 m −2 in the previous study versus US$0.05 m −2 in the present study, and higher selling prices, US$ 0.9 in the previous study versus US$0.23 in the present study per cabbage weighing 1.5 to 2.5 kg.…”
Section: Discussionsupporting
confidence: 87%
“…Similar profits to those obtained in the open field were only simulated by increasing the selling price by 50%. This confirmed a previous cost-benefit analysis conducted in Benin showing that the profitability of low tunnels for cabbage cultivation relies on the capacity to value the quality of products on the market (Vidogbéna et al, 2015a;Vidogbéna et al, 2015b). The higher profitability of the use of low tunnels reported in that study was also explained by higher insecticide costs, US $0.31 m −2 in the previous study versus US$0.05 m −2 in the present study, and higher selling prices, US$ 0.9 in the previous study versus US$0.23 in the present study per cabbage weighing 1.5 to 2.5 kg.…”
Section: Discussionsupporting
confidence: 87%
“…Le non-respect des doses et des délais avant récolte constitue un grand facteur de risque pour les consommateurs. La sécurité des exploitants pendant ou après les traitements phytosanitaires n'est pas non plus assurée, du Vidogbéna et al, 2015). La lutte biologique, avec l'emploi de certains champignons entomopathogènes comme Beauveria bassiana (Bals.-Criv.…”
Section: Méthodes Alternatives à La Lutte Chimiqueunclassified
“…Studies have shown that consumer knowledge of food safety across Africa is lower than Asia and may be associated with lower income [58]. However, targeted studies in Benin, Tanzania, and Kenya have shown that consumers have an awareness of potential health risks from agri-based foods in local markets and, in some cases, have demonstrated a willingness to pay more for safer products [59][60][61][62][63]. These studies demonstrate that with the correct consumer advice and awareness there can be a consumer based drive to improved food safety standards from both informal and formal markets.…”
Section: Building Capacitymentioning
confidence: 99%